(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Cytomorphological studies have revealed that a differentiated approach with the use of a two-component ointment based on silver ions combined with Povidone-iodine, taking into account the phase of the wound process in the treatment of wound infection, in contrast to traditional methods of treatment, has a number of positive aspects. In particular , the wound is cleared of infection by 2,0-2,5 days faster, the process of transition of the wound process from phase I to phase II is accelerated by 2,5-3,0 days, already on the 4-5 day of treatment, the cytological picture is replaced by an inflammatory-regenerative type of cytogram, which is characteristic of the uncomplicated course of the inflammatory process, and the number of purulent-necrotic, dysregenerative complications in the wound, which contributes to rapid scarring and epithelization of its surface.